TEACHER READINESS IN RESPONSE TO EDUCATIONAL TRANSFORMATION: A Comprehensive Bibliometric Study - Thahir, Muthahharah; Tamam, Badrud; Gunawan, Irvan (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study presents a bibliometric analysis of the scientific literature on